Strong limit of processes constructed from a renewal process - Bardina Xavier; Rovira Carles (Open Mathematics, 2023)
We construct a family of processes, from a renewal process, that have realizations that converge almost surely to the Brownian motion, uniformly on the unit time interval. Finally, we compute the rate of convergence in a particular case.